Ala®sil chemical characterization and toxicity evaluation: an example of the need for the Medical Device Regulation 2017/745 - Andrés-Iglesias, Cristina; Fernandez-Bueno, Ivan; Pastor-Idoate, Salvador; Coco-Martin, Rosa M.; Pastor, J. Carlos (Frontiers in Pharmacology, 2024)
The Ala ® sil infusion was on the market for clinical use under the Medical Devices Directive (MDD) 93/42/EEC as an irrigating solution based on polydimethyl siloxane (PDMS). The product was withdrawn in 2016, and to the best of our knowledge, it did not caused any health damage. A bibliographic review and experimental analysis were conducted to evaluate whether this CE-marked product could have been used in patients under the current MDR legislation.Only one study related to Ala ® sil clinical use was found, describing a pilot series of five patients. The authors rated the product as not helpful in three out of the five cases for internal searching of retinal breaks and in four out of the five cases for drainage of subretinal fluid. No other scientific papers or documentation were found regarding Ala ® sil's safety. Nevertheless, the product was introduced in the market after achieveing the CE marking.Analytical results from GC-MS and MALDI performed by our group showed that the polymer has a low molecular weight of 1000 g/mol. Several linear and cyclic low molecular weight components (LMWCs) were identified as impurities ranging from L3 to D8 with a molecular weight below 600 g/mol. Ala ® sil sample was cytotoxic after 24 hours of cell culture but non-cytotoxic after 72 hours, probably due to the cellular regeneration capacity of an immortalized cell line. Tissular cytotoxicity This is a provisional file, not the final typeset article revealed an increased apoptosis rate but without morphological modifications. Although Ala ® sil cannot be classified as cytotoxic, this substance appears to increase retinal cell death processes.This study supports the notion that the MDD was not functioning adequately to ensure the safety of medical devices. However, the current Medical Devices Regulation (MDR) 2017/745 imposes stricter standards to prevent the commercialization of medical devices without high-quality preclinical and clinical information, as well as precise clinical verification for their use -an information not available for Ala ® sil infusion-.